Measuring Involute Profile by using Polar Coordinate Method on Gear Measuring Center - Jing Tingdu (Jixie chuandong)
Recently,the polar coordinate method is successfully used to measure involute profile on gear measuring center and gear form grinding machine again. The measuring accuracy,efficiency,and convenience can be guaranteed and improved with the help of using some technology means,such as the calibrating the 3D（ or 2. 5D） probe accurately by means of ball gauge,using probe scanning technology to control measuring movement,using probe pre- offset to compensate the probe ball center offset and the method of specialized data gathering etc.